Lorenzo M. Tañada a centennial birthday tribute to a Filipino hero, 1898-1998. - Tañada, Lorenz (De La Salle University Information Imaging, Inc., 1998)
"This Web-CD is a multimedia compilation of photographs, historical documents & letters, news clippings, rare audio interviews and video clips on Lorenzo M. Tañada one of De La Salle University's most prominent alumni. These materials are currently archived at the De La Salle University Library's Tañada Memorabilia Room."-- CD-ROM back cove